Fatores que interferem na transição alimentar de crianças entre cinco e oito meses: investigação em Serviço de Puericultura do Recife, Brasil Factors that interfere in the food transition in children aged between five and eight months: an investigation of the childcare system in Recife, Brazil - Carmina Silva dos Santos; Luciane Soares de Lima; Marly Javorski (Instituto Materno Infantil de Pernambuco, 2007)
OBJETIVOS: identificar os lactentes de cinco a oito meses alimentados segundo as recomendações do Ministério da Saúde, atendidos no Serviço de Puericultura do Instituto Materno Infantil Professor Fernando Figueira - IMIP; detectar os principais problemas enfrentados pelas mães no processo de introdução alimentar; identificar o tipo de orientação recebida pelas mães para iniciar a dieta de transição. MÉTODOS: estudo transversal, descritivo, formado por 101 mães de crianças entre cinco e oito meses que haviam iniciado transição alimentar no período de abril a agosto de 2003, as quais foram solicitadas a participar do estudo antes da consulta, mediante os critérios de inclusão e exclusão. As crianças foram classificadas quanto à adequação às normas do Ministério da Saúde para transição alimentar. RESULTADOS: constatou-se que 79,2% dessas crianças não se adequavam às normas do Ministério da Saúde quanto à transição alimentar. Para o não seguimento a essas normas as mães apontaram, como principais motivos: recusa da criança (23,5%); interferência da avó (19%); praticidade do preparo/oferecimento do mingau em relação à alimentação salgada (17,7%). Quanto ao tipo de orientação, 97,4% afirmaram receber as orientações verbais e escritas no serviço. Na amostra estudada o enfermeiro e a avó foram os principais orientadores da transição alimentar, com 77% e 16%, respectivamente. CONCLUSÕES: apenas 20,8% das crianças apresentaram um padrão alimentar adequado, segundo as orientações do Ministério da Saúde. A mãe, principal responsável pelos cuidados da criança, sofreu influências do seu ambiente familiar, sobretudo da avó, e da sociedade em que está inserida. Também foi observado que, para a transição alimentar das crianças, 97,4% das mães recebeu orientação escrita além da orientação verbal. OBJECTIVES: to identify five- and eight-month old breast-feeding infants fed according to Health Ministry recommendations, cared for by the Instituto Materno Infantil Professor Fernando Figueira - IMIP Childcare Service; to ascertain the major problems faced by mothers in the process of weaning children; to identify the type of guidance given to mothers on how to initiate the food transition. METHODS: a descriptive, cross-sectional study was carried out involving 101 mothers/children aged between five- and eight-months who had initiated food transition between April and August 2003. The mothers were asked to participate in the study prior to a consultation with a physician, according to criteria for inclusion and exclusion. The children were classified in compliance with the norms established by the Ministry of Health regarding the food transition. RESULTS: it was found that 79.2% of the children did not meet the Ministry of Health's norms for food transition. The reasons for not complying with the norms mentioned by mothers were as follows: refusal on the part of the child (23.5%); interference of grandmothers (19%); practicality of preparation/provision of porridge compared with solid food (17.7%). As for the type of guidance, 97.4% claimed to have received spoken and written guidance at work. In the case of the sample studied, nurses and grandmothers had played a major role in providing guidance on the food transition, 77% and 16%, respectively. CONCLUSION: only 20.8% of the children displayed an adequate feeding standard complying with the norms of the Ministry of Health. The mother, who is the one usually responsible for child care, was influenced by family members, especially the grandmother, and by society at large. It was also found that the majority (97.4%) of the mothers received written as well as spoken guidance.